2009
DOI: 10.5194/bg-6-877-2009
|View full text |Cite
|
Sign up to set email alerts
|

Primary production during nutrient-induced blooms at elevated CO<sub>2</sub> concentrations

Abstract: Abstract.A CO 2 enrichment experiment (PeECE III) was carried out in 9 mesocosms in which the seawater carbonate system was manipulated to achieve three different levels of pCO 2 . At the onset of the experimental period, nutrients were added to all mesocosms in order to initiate phytoplankton blooms. Primary production rates were measured by in-vitro incubations based on 14 C-incorporation and oxygen production/consumption. Size fractionated particulate primary production was also determined by 14 C incubatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
80
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 58 publications
8
80
3
Order By: Relevance
“…Tolerance of CO 2 levels up to ∼ 1000 µatm has often been observed in natural phytoplankton communities in regions exposed to fluctuating CO 2 levels. In these communities, increasing CO 2 often had no effect on primary productivity (Tortell et al, 2000;Tortell and Morel, 2002;Tortell et al, 2008b;Hopkinson et al, 2010;Tanaka et al, 2013;Sommer et al, 2015;Young et al, 2015;Spilling et al, 2016) or growth (Tortell et al, 2008b;Schulz et al, 2013), although an increase in primary production has been observed in some instances (Riebesell, 2004;Tortell et al, 2008b;Egge et al, 2009;Tortell et al, 2010;Hoppe et al, 2013;Holding et al, 2015). These differing responses may be due to differences in community composition, nutrient supply, or ecological adaptations of the phytoplankton community in the region studied.…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 76%
See 1 more Smart Citation
“…Tolerance of CO 2 levels up to ∼ 1000 µatm has often been observed in natural phytoplankton communities in regions exposed to fluctuating CO 2 levels. In these communities, increasing CO 2 often had no effect on primary productivity (Tortell et al, 2000;Tortell and Morel, 2002;Tortell et al, 2008b;Hopkinson et al, 2010;Tanaka et al, 2013;Sommer et al, 2015;Young et al, 2015;Spilling et al, 2016) or growth (Tortell et al, 2008b;Schulz et al, 2013), although an increase in primary production has been observed in some instances (Riebesell, 2004;Tortell et al, 2008b;Egge et al, 2009;Tortell et al, 2010;Hoppe et al, 2013;Holding et al, 2015). These differing responses may be due to differences in community composition, nutrient supply, or ecological adaptations of the phytoplankton community in the region studied.…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 76%
“…Kim et al, 2006;Hopkinson et al, 2010;Riebesell et al, 2013;Paul et al, 2015;Bach et al, 2016;Bunse et al, 2016). Studies in the Arctic reported increases in phytoplankton primary productivity, growth, and organic matter concentration at CO 2 levels ≥ 800 µatm under nutrient-replete conditions (Bellerby et al, 2008;Egge et al, 2009;Engel et al, 2013;Schulz et al, 2013), whilst the bacterial community was unaffected (Grossart et al, 2006;Allgaier et al, 2008;Paulino et al, 2008;Baragi et al, 2015). These studies also highlight the importance of nutrient availability in the community response to elevated CO 2 , with substantial differences in primary and bacterial productivity, chlorophyll a (Chl a), and elemental stoichiometry observed between nutrient-replete and nutrient-limited conditions Schulz et al, 2013;Sperling et al, 2013;Bach et al, 2016).…”
mentioning
confidence: 99%
“…Riebesell et al speculated that TEP may have played a significant role in the transformation of DOC to POC and the sinking of POC from the upper layer of the mesocosms with high pCO 2 . However, analysis of the TEP concentrations from the same experiment by Egge et al (2009) showed no difference in TEP production between the different pCO 2 treatments. Recently, experiments using mesocosms in Arctic waters showed enhanced production of DOC by phytoplankton grown under elevated CO 2 (Engel et al, 2013).…”
Section: Ocean Acidificationmentioning
confidence: 99%
“…Increasing photosynthesis with elevated CO 2 is observed for some cyanobacteria (Synechococcus) but not others (Prochlorococcus) , and many eukaryotic phytoplankton species, most notably diatoms, have carbon concentrating mechanisms that diminish almost entirely the sensitivity of photosynthesis to CO 2 variations (Tortell et al, 1997). Bottle incubations and mesocosm experiments with natural plankton communities indicate only a weak sensitivity of primary production to CO 2 , although limited CO 2 fertilization is observed in some cases (Tortell et al, 2008;Egge et al, 2009). There are suggestions that the carbon content of phytoplankton cells may increase under high CO 2 conditions (Riebesell et al, 2007), but any physiological changes appear to be quite subtle, and there is conflicting evidence from different studies on how plankton carbon/nitrogen stoichiometry varies with CO 2 .…”
Section: Ocean Acidification and Microbesmentioning
confidence: 99%